Unfractionated and Low-Molecular-Weight Heparin and the Phosphodiesterase Inhibitors, IBMX and Cilostazol, Block Ex Vivo Equid Herpesvirus Type-1-Induced Platelet Activation - Stokol, Tracy; Serpa, Priscila B. S.; Zahid, Muhammad N.; Brooks, Marjory B. (Frontiers in Veterinary Science, 2016)
Equid herpes virus type-1 (EHV-1) is a major pathogen of horses, causing abortion storms and outbreaks of herpes virus myeloencephalopathy. These clinical syndromes are partly attributed to ischemic injury from thrombosis in placental and spinal vessels. The mechanism of thrombosis in affected horses is unknown. We have previously shown that EHV-1 activates platelets through virus-associated tissue factor-initiated thrombin generation. Activated platelets participate in thrombus formation by providing a surface to localize coagulation factor complexes that amplify and propagate thrombin generation. We hypothesized that coagulation inhibitors that suppress thrombin generation (heparins) or platelet inhibitors that impede post-receptor thrombin signaling (phosphodiesterase [PDE] antagonists) would inhibit EHV-1-induced platelet activation ex vivo. We exposed platelet-rich plasma collected from healthy horses to the RacL11 abortigenic and Ab4 neuropathogenic strains of EHV-1 at 1 plaque forming unit/cell in the presence or absence of unfractionated heparin (UFH), low-molecular-weight (LMWH) heparin or the PDE inhibitors, 3-isobutyl-1methylxanthine (IBMX) and cilostazol. We assessed platelet activation status in flow cytometric assays by measuring P-selectin expression. We found that all of the inhibitors blocked EHV-1- and thrombin-induced platelet activation in a dose-dependent manner. Platelet activation in PRP was maximally inhibited at concentrations of 0.05 U/mL UFH and 2.5 μg/mL LMWH. These concentrations represented 0.1 to 0.2 U/mL anti-Factor Xa activity measured in chromogenic assays. Both IBMX and cilostazol showed maximal inhibition of platelet activation at the highest tested concentration of 50 μM but inhibition was lower than that seen with UFH and LMWH. Our results indicate that heparin anticoagulants and strong non-selective (IBMX) or isoenzyme-3 selective (cilostazol) PDE antagonists inhibit ex vivo EHV-1-induced platelet activation. These drugs have potential as adjunctive therapy to reduce the serious complications associated with EHV-1-induced thrombosis. Treatment trials are warranted to determine whether these drugs yield clinical benefit when administered to horses infected with EHV-1.